Two proposed approaches to uphold QoS during handover in LTE-A systems - Jouili, Imen; Hassine, Kawther; Frikha, Mounir (2016 5th International Conference on Multimedia Computing and Systems (ICMCS), 2016)
Given the rapid expansion of Long Term Evolution (LTE) systems, Quality of Service (QoS) have got to be a key factor when it comes to users' Quality of Experience (QoE). Operators and service providers are, more than ever, focused to provide high data rate and high reliable services especially under high mobility circumstances. However, in high speed case, QoS in LTE-Advanced (LTE-A) systems poses quite a challenge especially for real-time services. Within highly dynamic nodes, handover occurs so often that currently used resource in a "source node" could be not available in the "target node" during the handover decision. In this paper, we present two approaches for resource allocation during high speed handover scenarios. The first approach is an Extended Soft Handover Algorithm (EHSA) based on Carrier Aggregation (CA) and Coordinated Multiple Point (CoMP) technologies. The second approach is a Network Coding Algorithm (NCA), based on Network Coding and CoMP technologies. A comparative study proved that both methods optimize resource assignment and sustain better levels of QoS during handover decision by reference to the conventional CoMP handover. Nevertheless, the ESHA based approach seems to fit most, real time applications. While NCA approach, handles more efficiently scarce resources case.